National Biosafety Management System: A Combined Framework Approach Based on 15 Key Elements - Orelle, Arnaud; Nikiema, Abdoulaye; Zakaryan, Arsen; Albetkova, Adilya A.; Rayfield, Mark A.; Peruski, Leonard F.; Pierson, Antoine; Kachuwaire, Obert (Frontiers in Public Health, 2021)
The pervasive nature of infections causing major outbreaks have elevated biosafety and biosecurity as a fundamental component for resilient national laboratory systems. In response to international health security demands, the Global Health Security Agenda emphasizes biosafety as one of the prerequisites to respond effectively to infectious disease threats. However, biosafety management systems (BMS) in low-medium income countries (LMIC) remain weak due to fragmented implementation strategies. In addition, inefficiencies in implementation have been due to limited resources, inadequate technical expertise, high equipment costs, and insufficient political will. Here we propose an approach to developing a strong, self-sustaining BMS based on extensive experience in LMICs. A conceptual framework incorporating 15 key components to guide implementers, national laboratory leaders, global health security experts in building a BMS is presented. This conceptual framework provides a holistic and logical approach to the development of a BMS with all critical elements. It includes a flexible planning matrix with timelines easily adaptable to different country contexts as examples, as well as resources that are critical for developing sustainable technical expertise.